The Importance Of Taxawareness In Supporting National Development - Karona Cahya Susena; Nenden Restu Hidayah; Rico Hasudungan Nainggolan (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2025)
Taxes play a vital role as the backbone of national development, serving as the primary source of state revenue to finance infratructure, education, healthcare, and social welfare programs. Public awareness of tax compliance is crucial for ensuring the sustainability of these efforts. This article explores the importance of tax awareness in supporting national progress, particularly its role in funding publiic infrastructure, enhancing social welfare, and maintaining economic stability. Furthermore, it addresses the negative impacts of low tax compliance and proposes strategies to increase tax awareness, such as education, transparency, simplifying tax systems, and enforcing regulations. Improving tax awareness is essential to fostering shared responsibility and creating a prosperous and equitable society.